Inovasi Budidaya Sawi Hidroponik Berbasis Otomasi Greenhouse untuk Meningkatkan Produktivitas dan Efisiensi - Tesyahtul Senni Khairiyah; Nazwa Mirandes; Ellisa Umami; Desta Fauziah Setiawan; Adinda Aulia Dinasta; Hafiz Reyhan; Sayyida Shalikha Asy Syamsi; Nishtu Nur Holisah; Requelme Citra Purnama; Agief Julio Pratama; M. Iqbal Nurulhaq; Ririh Sekar Mardisiwi; Ratih Kemala Dewi; Restu Puji Mumpuni; Edi Wiraguna (International Forum of Researchers and Lecturers, 2026)
Hydroponic cultivation of mustard greens (Brassica juncea L.) in greenhouses is an effective alternative for overcoming land limitations, particularly in urban areas. Hydroponic systems enable plants to obtain nutrients optimally through the application of the Nutrient Film Technique (NFT) and Deep Flow Technique (DFT), thereby promoting more efficient plant growth. In addition, the success of hydroponic mustard cultivation is influenced by environmental control, including temperatures ranging from 15–35°C and relative humidity levels of 70–90%. Plant nutrient requirements are supplied through an AB Mix nutrient solution with a pH range of 5.5–6.5 and an electrical conductivity (EC) value of 1.5–3.0 mS/cm. This review aims to analyze various factors affecting the growth of hydroponic mustard greens, including nutrient management, environmental conditions, and biological pest and disease control using beneficial agents such as Trichoderma and Bacillus. Furthermore, this study discusses several technical and economic challenges that may influence cultivation success. The findings indicate that hydroponic systems can significantly improve crop productivity and yield quality, reduce the use of chemical pesticides, and support the implementation of sustainable and environmentally friendly urban agriculture in Indonesia.